The Digestive System Content of Mastacembelus mastacembelus (Banks & Solander, 1794) Inhabiting in Karakaya Dam Lake (Malatya-Turkey) - Pala, Gunes; Tellioglu, Ayda; Eroglu, Mucahit; Sen, Dursun (Central Fisheries Research Inst, 2010)
In this study, digestive system contents of a total of 126 Mastacembelus mastacembelus (Banks & Solander, 1794) obtained from Karakaya Darn Lake were examined by means of Geometric Index of Importance (GII). In the digestive system content of examined fish, Bacillariophyta (16 taxa), Chlorophyta (6 taxa), Cyanophyta (5 taxa), Dinophyta (1 taxon) and Euglenophyta (1 taxon) which belong to plants and Rotifera (14 taxa), Cladocera (4 taxa), Copepoda (2 taxa) and Pisces (3 taxa) which belong to animals have been found. The percentage of organisms in the all organisms were determined respectively as Bacillariophyta (32.79%), Rotifera (29.83%), Cyanophyta (16.20%), Chlorophyta (14.36%), Cladocera (3.40%), Copepoda (2.69%), Euglenophyta (0.61%), Pisces (0.09%) and Dinophyta (0.03%).
Karakaya baraj gölë (Malatya-Türkiye)'nde ya?ayan mastacembelus mastacembelus (Banks & Solander, 1794)'un sindirim sistemi içeri?i
Keywords: Mastacembelus mastacembelus; digestive system; stomach contents; Karakaya Dam Lake